1994
DOI: 10.1002/bem.2250150307
|View full text |Cite|
|
Sign up to set email alerts
|

Empirical test of an ion parametric resonance model for magnetic field interactions with PC‐12 cells

Abstract: A companion paper describes a predictive ion parametric resonance (IPR) model of magnetic field interactions with biological systems based on a selective relation between the ratio of the flux density of the static magnetic field to the AC magnetic field and the charge-to-mass ratio of ions of biological relevance. Previous studies demonstrated that nerve growth factor (NGF)-stimulated neurite outgrowth (NO) in PC-12 cells can be inhibited by exposure to magnetic fields as a function of either magnetic field f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 48 publications
2
89
1
Order By: Relevance
“…It has been found by Blackman et al [1985] that the ambient static magnetic fields (SMF) can significantly influence the effects of ELF fields. The importance of SMF for the ELF effects has been confirmed in several studies [Lednev, 1991;Belyaev et al, 1994;Blackman et al, 1994;Fitzsimmons et al, 1994;Prato et al, 1995]. Therefore, the effects of weak ELF are usually observed only under specific combinations of frequency, amplitude, and SMF.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…It has been found by Blackman et al [1985] that the ambient static magnetic fields (SMF) can significantly influence the effects of ELF fields. The importance of SMF for the ELF effects has been confirmed in several studies [Lednev, 1991;Belyaev et al, 1994;Blackman et al, 1994;Fitzsimmons et al, 1994;Prato et al, 1995]. Therefore, the effects of weak ELF are usually observed only under specific combinations of frequency, amplitude, and SMF.…”
Section: Introductionmentioning
confidence: 76%
“…The ELF effects are also dependent on variety of physical and biological parameters Blackman et al, 1988Blackman et al, , 1994Belyaev et al, 1994Belyaev et al, , 1999aPrato et al, 1995]. Moreover, exposure of human lymphocytes or V79 SPD8 cells to magnetic field at 8 Hz (21 mT rms) resulted in DNA fragmentation [Belyaev et al, 2001c;Olsson et al, 2001].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, their ELF-EMF coils were placed at the top and bottom, whereas ours were placed on each side of the growth chambers. This could also be a potential explanation of the differences because Blackman et al (34)(35)(36) demonstrated that ELF-EMF perpendicular to the static fields of the earth had the greatest effect on Table 2. NEL, no effect level.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several decades of investigation, controversy still surrounds the issue of whether these ELF MFs can cause measurable changes in biological systems and whether these changes are harmful. Nonetheless, a large number of studies, both in vitro and in vivo, strongly suggest that changes can occur, even though the mechanism of interaction remains obscure [Polk, 1991;Blackman et al, 1994;Graham et al, 1996;Beale et al, 1997;National Research Council, 1997].…”
Section: Introductionmentioning
confidence: 99%